Evaluation of Physical and Chemical Characteristics of Male and Female Ducks Carcasses at Different Ages - Jassim, Jafar M.; Mossa, Riyad K.; Al-Assadi, Majid H.; Gong, Yanzhang (Pakistan Journal of Nutrition, 2011)
This study was conducted at Agricultural Research Station, College of Animal Sciences, Agriculture University of Huazhong, China, for the period of 27/3/2009 to 27/6/2009. The aim was to determine the effect of strain, sex and age at slaughtering on quality traits of meat of two breeds of ducks (Cherry Valley and Chinese local duck). A total of 120 chicks (60 from each breed) one day old were used. A sample of birds was slaughtered at 6, 8, 10 and 12 weeks of age. Muscle pH at 0.25, 6 and 24 h, meat color at 24 h of breast and leg muscles, water holding capacity and proportion of losing fluids were measured. Breeds had no significant effect on breast or legs muscle PH, however, Leg muscle showed higher (p<0.05) pH at the storing period of 0.25 and 24 h than breast. Breast muscle of local Chinese ducks showed higher (p<0.05) redness (a) and less transparency (L) in comparison with Cherry Valley ducks. Males breast muscle were more (p<0.05) yellowness (b) in comparison with that of female for both breeds. Viscous of Cherry Valley ducks were higher (p<0.05) than that of Chinese local ducks. Both breeds did not exhibit significant differences. Local Chinese ducks breast muscle males showed significantly (p<0.05) higher water holding capacity than that of Cherry Valley breed for both sexes. Muscle extensibility and muscle shearing value and drip loss percentage of Cherry Valley carcass were higher (p<0.05) than that of local Chinese ducks in preceding ages.